PEREMPUAN DAN KEKERASAN DALAM RUMAH TANGGA: DISKURSUS HAM DALAM KARYA NAWAL SA’DAWI - Kurniati, Kurniati (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2019)
Domestic violence that commonly makes women as the victims is a violation of the human rights of women as worthy human beings. The human rights discourse found in Nawal Sa'dawi works has provided a framework of social criticism of the reality of domestic violence that takes refuge in justification in the name of religion. Human rights discourse that is contained in Nawal Sa'dawi's works should not be trapped in the literary texts but must be transformed in context both in domestic households in particular and in social environment in general.